RARE-02.RE-IRRADIATION FOR RECURRENT CRANIOPHARYNGIOMA - Foran, Sarah (Neuro Oncol, 2020)
PURPOSE: Patients with recurrent craniopharyngioma after radiotherapy (RT) have few treatment options. At our institution, re-irradiation has been offered to selected individuals with recurrent craniopharyngioma not suitable for further surgery, intracystic therapy or targeted agents. METHODS: A retrospective study was performed of patients with craniopharyngioma treated with two courses of fractionated RT. First RT (RT1) prescriptions ranged from 50–54 Gy in 25–30 fractions; re-irradiation (RT2) prescriptions were 54 Gy in 30 fractions with full, in-field overlap of dose. The maximum dose to organs-at-risk (brainstem, optic structures) were maintained at or below the prescription dose. There was no cumulative dose limit to any structure. RESULTS: We identified four patients. Median RT1-to-RT2 interval was 5.8 years (range, 4.7–20.4). Cumulative maximum doses to optic chiasma and nerves were >100 Gy in all four patients. With a median follow-up of 33 months after RT2, three patients had disease control and are alive at 9, 23 and 42 months from RT2; one patient developed progressive disease and died 33 months after RT2. In three evaluable patients, vision remained stable or improved after RT2; the remaining one patient had no light perception prior to re-irradiation. Two patients had neuropsychological testing before and after RT2; neurocognitive domains were generally stable in one patient but working memory declined in the second patient. CONCLUSIONS: Despite exceeding usual tolerances for optic chiasm and nerves, visual outcomes were stable in all living patients. Re-irradiation should be discussed as a treatment option for patients with recurrent craniopharyngioma but without other therapeutic options.